Financial Performance of BUMN Go Public on The Indonesian Stock Exchange on Company Value - Titania Anggraini; Isni Andriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze company performance based on the financial aspects of BUMN: Return On Equity, Return On Investment, Cash Ratio, Current Ratio, Collection Periods, inventory turnover, total asset turnover, ratio of own capital to total assets of BUMN companies go public listed on the Indonesian Stock Exchange on company value. The research period is 5 years, namely the 2018-2022 period. This study uses a quantitative approach. This research method uses panel data regression analysis with a research period of 2018-2022 with estimates ordinary least square (OLS), random effect model (REM), and fixed effect model (FEM), and the population used in this research was 114 BUMN companies and the sampling method was using samples with certain criteria. The sample used was 23 BUMN go public companies listed on the Indonesia Stock Exchange. The research results show that shareholder returns (ROE) have a significant positive effect on company value. Cash ratio, current ratio, Return on Investment, Inventory Turnover, Collection Periods, total asset turnover and the ratio of own capital to total assets do not have a significant effect on company value.